Development and Characterization of LDPE/EVA Films Incorporating Carvacrol Essential Oil with Antifungal Activity - Konstantinos Safakas; Georgia C. Lainioti; Pinelopi Koutsodima; Panagiota Stathopoulou; Athanasios Ladavos (Foods)
The development of antimicrobial and antioxidant packaging materials is critical for improving food safety and extending shelf life. This study aimed to design and characterize low-density polyethylene (LDPE) and poly(ethylene-co-vinyl acetate) (EVA) films incorporating organically modified montmorillonite (OMt) nanocarriers loaded with carvacrol (C) and thymol (T) essential oil components. The incorporation of carvacrol and thymol into OMt was conducted through an evaporation/adsorption method without the use of organic solvents. In the next step, LDPE, EVA and OMtC or OMtT were melt-compounded in order to obtain films. Characterization of the bioactive nanocarriers and films was performed through X-ray diffraction (XRD), tensile testing, oxygen permeability measurements (OTR) and antioxidant assays. Films LDPE/EVA/OMtC and LDPE/EVA/OMtT showed improved mechanical strength and antioxidant activity, with IC50 values between 0.32 and 0.52 mg/mL. Film with component weight ratio LDPE/EVA/OMtC equal to 80/10/10 also demonstrated enhanced barrier properties and significantly inhibited fungal growth on baguette bread for up to 60 days. These findings highlight the potential of these bioactive films to improve the microbial safety and shelf life of bakery products.